2006
DOI: 10.1002/uog.2768
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of the vermis as a cause of enlarged cisterna magna on prenatal imaging

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…Indeed, we found that in the sagittal plane, the vermis was very well delineated, and its longitudinal diameter could be measured. 3,17 This view may sometimes be difficult to obtain. Although in a vertex presentation, the vaginal approach can improve brain visualization, when the fetus lies in a breech presentation, it can require considerable time and expertise to obtain an adequate sagittal view.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that in the sagittal plane, the vermis was very well delineated, and its longitudinal diameter could be measured. 3,17 This view may sometimes be difficult to obtain. Although in a vertex presentation, the vaginal approach can improve brain visualization, when the fetus lies in a breech presentation, it can require considerable time and expertise to obtain an adequate sagittal view.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kölble et al [14] found normal karyotypes in all 7 DWM cases tested. Several studies support the theory that isolated MCM malformation has a favourable prognosis of normal developmental outcome [13,17,18], and isolated DWC fetuses can expect a good prognosis in up to 67% [13]. Knowledge of the long-term outcome on PBP is limited to 6 case studies of adults diagnosed after presenting with hydrocephaly [19].…”
Section: Introductionmentioning
confidence: 99%
“…2 Fetal posterior fossa anomalies range from benign asymptomatic conditions to severe abnormalities associated with neurologic impairment. [3][4][5][6] The most frequent of these anomalies, Blakes pouch cyst, vermian hypoplasia, and Dandy-Walker malformation, have a similar imaging appearance 7,8 but different vermian biometry and, therefore, different prognoses. 9 Many anomalies of the posterior fossa can be depicted with sonography alone.…”
mentioning
confidence: 99%